Cytokeratin expression in gastrointestinal stromal tumors: Morphology, meaning, and mimicry - Yetish Sing; Pratistadevi K Ramdial; Amsha Ramburan; Vikash Sewram (Wolters Kluwer Medknow Publications, 2014)
Background: Gastrointestinal stromal tumors (GISTs) are biologically distinctive neoplasms harboring KIT and PDGFRA mutations. Cytokeratin expression in GISTs is an under-recognized diagnostic pitfall, especially in high grade GISTs with limited biopsy material and from metastatic sites. Materials and Methods: We evaluated the histomorphology and expression of four 'broad-spectrum' cytokeratin markers, AE1-AE3, CAM 5.2, MNF-116, and 34βE12 in 64 GISTs diagnosed over a 68-month period. Individual cytokeratins 5, 6, 7, 8, 14, 17, 18, 19, and 20 were investigated in the 'broad-spectrum' cytokeratin-positive GISTs. Results: Of 64 GISTs, 10 (15%) demonstrated cytokeratin immunopositivity. All 10, considered high risk by the National Institutes of Health consensus approach, were immunopositive for CAM 5.2 and MNF-116. Seven were AE1-AE3 immunopositive. Cytokeratins 8 and 18 were confirmed in 10 and 9 GISTs, respectively. One GIST demonstrated biphasic morphology with cytokeratin immunonegativity in low-grade spindle and immunopositivity in high-grade epithelioid foci. KIT and PDGFRA mutational analysis, undertaken in 5/10 cytokeratin-positive GISTs, harbored KIT exon 11 mutations. Conclusion: We hypothesize that cytokeratin expression exclusively in high risk GISTs is a consequence of tumor progression. Given the increasing number of commercially available broad-spectrum cytokeratin immunomarkers, including those reacting with cytokeratins 8 and 18, cytokeratin-positive GISTs must be differentiated from carcinomas, melanomas, and a range of cytokeratin-positive sarcomas to ensure optimal patient management and prognostication.